(untitled) (LEARNing Landscapes, 2022)
College students have experienced unique life disruptions and losses due to the COVID-19 pandemic. We conducted this study to gain an understanding of how the pandemic has affected the lifestyle of college students. Findings included: major changes in perceived well-being related to living at home with families, balancing online classes and work, stress and boredom related to isolation from peers, and coping strategies, including substance abuse and physical activity. Research and practice implications are related to increasing opportunities and activities to promote a sense of belonging for students, and also for increased accessible student support services on college campuses.